Role of Magnetic Resonance Imaging (MRI) in Diagnosing and Classifying Mullerian Duct Anomalies: A Case Series - Bhavya Kataria; Shibani Mehra (Medical Science: Trends and Innovations Vol. 1, 2025)
Background: The pair of mullerian ducts in females is responsible for the development of the female reproductive system, namely, fallopian tubes, uterus, cervix, and upper part of the vagina. Mullerian duct anomalies (MDAs) arise from the aberrant development of the uterus, cervix, and vagina, impacting the potential for successful conception and full-term pregnancy. This category encompasses a diverse range of developmental defects, leading to a spectrum of clinical presentations such as amenorrhea, infertility, recurrent miscarriages, intrauterine growth retardation, malposition of the fetus, preterm labor, and retained placenta. Case(s): In this study, 17 cases of MDA are presented with a wide array of clinical manifestations. The varied symptoms included amenorrhea, infertility, repeated miscarriages, intrauterine growth retardation, malposition of the fetus, preterm labor, and retained placenta. Accurate categorization of these cases is crucial for determining the appropriate surgical intervention. While ultrasonography aids in the initial diagnosis of MDA, our focus on accurate classification necessitates the use of magnetic resonance imaging (MRI). Conclusion: The findings underscore the significance of MRI in precisely categorizing MDA, and facilitating effective management strategies. The 17 cases presented demonstrate the diverse spectrum of MDA manifestations, emphasizing the need for tailored surgical interventions for successful conception and optimal pregnancy outcomes. The use of MRI proves instrumental in guiding clinical decisions, offering a comprehensive understanding of MDA, and informing targeted interventions to enhance reproductive success. Female infertility can be attributed to MDA, and in many cases of MDA, appropriate surgery can lead to successful conception. Furthermore, in some cases, surgery cannot lead to conception. Thus, correct classification of individual cases with MRI is essential for not only successful conception through appropriate surgery but also for avoidance of unnecessary surgical intervention.